اقبالؒ اور اکبرؒ کی اردو شاعری میں قرآنی احکام، تلمیحات اور اثرات کا تحقیقی جائزہ (Al-Qamar, 2024)
Akbar Ilahabadi is one of Iqbal’s elder contemporaries. Dr, Sir Muhammad Iqbal used to call Akbar Ilahabadi as his Leader (Pir & Murshid). He went to Ilahabad three times to meet Akbar Ilahabadi. There are significant differences in the style & art of the two poets, but their theory of thinking & views is almost identical. Akbar’s poetry is graceful, humorous & simple. He used lot of English words in his poetry. While Iqbal’s poetry is serious & wise, Except for the poetry which is known as Akbari Iqbal. Both poets made poetry a source for the awakening & revival of Islam in the Muslim Ummah. Qur’anic verses, Talmihat (Qur’anic allusions) & influences abound in the poetry of both poets. The Qur’anic influences in the poetry of both poets can be described in the light of the Mohkam verses of the Holy Qur’an. Urdu poetry of both poets is very influential & popular. A study of their poetry reveals that both poets had a special attachment to the Qur’anic sciences.Both poets did not consider English culture to be better for the Muslims of the Subcontinent. Both advised the Muslims to pursue education & adopt Islamic values. Undoubtedly, both scholars had a profound effect on the Muslim Ummah. The following article examines the Qur’anic influences on the poetry of both poets.
Keywords: Akbar, Iqbal; Ilahabadi; Poetry; Qur’anic Verses